THE INVOLVEMENT OF ARTIFICIAL INTELLIGENCE (AI) IN ENHANCING COMMUNICATION SKILLS OF ENGLISH LANGUAGE LEARNERS - Abdul Rehman Soomro; Dr. G. Akbar Tumrani; Zaheer Ahmed Bango; Sonal Khan Maitlo (International Journal of Contemporary Issues in Social Sciences, 2023)
The current research delves into the realm of artificial intelligence (AI) and its impact on enhancing the communication skills of English Language Learners (ELLs) within the Khairpur district. Employing a qualitative research method, the study unfolded in the backdrop of Khairpur Mir’s Sindh, focusing on a diverse population of 200 students from various departments of the university. This research sought to understand the nuances of AI’s involvement in strengthening communication skills among male and female students. Data collection was conducted through email and Whats App, targeting undergraduate students. A qualitative approach was taken using a 5-point Likert scale to gather responses, and the collected data underwent thorough statistical analysis presented in columns. The study’s outcomes were the confirmatory, indicating that the utilization of Artificial Intelligence (AI) proves beneficial for English Language Learners (ELLs). Furthermore, the results suggest that ELLs can effectively harness AI to ameliorate their overall communication skills, highlighting the promising potential of AI in language education.